Risk, Temptation, and Efficiency in the One-Shot Prisoner's Dilemma - Simon Gaechter; Kyeongtae Lee; Martin Sefton; Till O. Weber (Center for Economic Studies and ifo Institute (CESifo), 2021)
The prisoner's dilemma (PD) is arguably the most important model of social dilemmas, but our knowledge about how a PD's material payoff structure affects cooperation is incomplete. In this paper we investigate the effect of variation in material payoffs on cooperation, focussing on one-shot PD games where efficiency requires mutual cooperation. Following Mengel (2018) we vary three payoff indices. Indices of risk and temptation capture the unilateral incentives to defect against defectors and co-operators respectively, while an index of efficiency captures the gains from cooperation. We conduct two studies: first, varying the payoff indices over a large range and, second, in a novel orthogonal design that allows us to measure the effect of one payoff index while holding the others constant. In the second study we also compare a student and non-student subject pool, which allows us to assess generalizability of results. In both studies we find that temptation reduces cooperation. In neither study, nor in either subject pool of our second study, do we find a significant effect of risk.
Keywords: A13; C91; 330; prisoner's dilemma; cooperation; temptation; risk; efficiency